Hydrostatic reduction of intussusception in children: a single centre experience - Chukwubuike, Kevin Emeka (Pan Afr Med J, 2020)
INTRODUCTION: intussusception is a common surgical emergency in children especially in infants. Treatment of intussusception could be non-operative or operative. Non-operative treatment (hydrostatic reduction) of intussusception is increasingly being practiced in developing countries. METHODS: this was a review of our experience in the hydrostatic reduction of intussusception in children at a teaching hospital in Enugu, Nigeria. This study covered an 18-months period, October 2017 to March 2019. Patients on presentation were resuscitated, appropriate investigations done and prepared for surgery before the hydrostatic reduction (using normal saline) was carried out. Patients with features of peritonitis and marked abdominal distension were excluded from hydrostatic reduction. RESULTS: twenty patients who had 21 episodes of intussusception were analyzed. One patient had a recurrence that necessitated repeat hydrostatic reduction. Eighty percent of the patients were male. The mean and peak age of the patients was 8 months and 6 months respectively. Significant number of the patients presented after 48 hours of onset of their symptoms. Abdominal pain was the predominant presenting symptom. Twenty percent and fifteen percent of the patients had a history of preceding gastrointestinal and respiratory infections preceding the intussusception respectively. Ileocolic intussusception was the most common type and the most distal end of the intussusception was at the transverse colon. Hydrostatic reduction was successful in 13 patients (65%). CONCLUSION: hydrostatic reduction is a simple and effective method of treatment of intussusception. However, early presentation and proper patient selection is necessary for optimal outcome.